Reactive Spring Boot, 2nd Edition - Long, Josh (Addison-Wesley Professional, 2020)
6 Hours of Video Instruction Spring is the most used framework for building services and applications and getting them to production. Today's applications need to scale more and more to handle more users and content with the increasing demand. Reactive Spring Boot LiveLessons, by Josh Long, Spring Developer Advocate, introduces key concepts of reactive programming and examines different aspects of the Spring ecosystem that lend themselves to the functional and reactive style of programming. These videos not only show you where to start and how to build these applications, but they also provide a solid foundation that will allow you to apply the skills learned to other parts of the Spring ecosystem that build on these core concepts. About the Instructor Josh Long (starbuxman) is the first Spring Developer Advocate. Josh is a Java Champion, author of many books (including O'Reilly's Cloud Native Java: Designing Resilient Systems with Spring Boot, Spring Cloud, and Cloud Foundry and the self-published Reactive Spring) and six best-selling video trainings (including Building Microservices with Spring Boot LiveLessons with Phil Webb), and an open-source contributor (Spring Boot, Spring Integration, Spring Cloud, Activiti, and Vaadin). Skill Level Intermediate Learn How To Examine the different aspects of the Spring ecosystem that lend themselves to the functional and reactive style of programming Explore Reactive Data Access using Spring Data and Spring Data MongoDB Understand the Reactive Streams specification as a compatibility layer and how to use the Reactive Stream types as a mechanism for interoperability across OS projects Test reactive applications How to consume data from a publisher in Spring Integration and how to consume data from a publisher in Spring Cloud Stream Use Spring Cloud Function Build Edge Services Who Should Take This Course Existing or new Spring users Experienced Java developers Course Requirements Basic Java familiarity. The course uses Java 8, although Spring Boot and most Spring projects support Java 6. Lesson Descriptions Lesson 1, "Basics," examines what motivates the move to reactive programming and how it is supported in the Reactive Streams specification. Lesson 2, "Data," covers the importance of data and how Spring supports non-blocking data access for any NoSQL and SQL data stores. Lesson 3, "HTTP Services," focuses on what reactive programming means in an HTTP environment. It introduces functional reac ...
Online resource; Title from title screen (viewed February 13, 2020)
Keywords: Electronic videos